Extracting Complex Refractive Index from Polycrystalline Glucose with Self-Referenced Method for Terahertz Time-Domain Reflection Spectroscopy. Issue 7 (July 2016) - Zhang, Yu; Zhang, Lin; Sun, Ping; He, Yingfeng; Zou, Yun; Deng, Yuqiang
A self-referenced method for extracting the complex refractive index of material was proposed. The method utilized signals reflected from the front and rear surfaces of a slice sample as reference and sample signals, respectively. Before using the self-referenced method, a hybrid filtering technique for eliminating systematic and random noises of time-domain terahertz reflection spectroscopy was used. A terahertz reflection spectrum of crystalline glucose was measured and three feature absorption peaks were obtained from 0.2 to 2.0 THz. We suggest that intermolecular vibrational modes may contribute to the observed absorption spectra in the THz frequency range.